Six year follow-up of a clinical sample of self-harm patients - Sinclair, J; Hawton, K; Gray, A (Elsevier, 2010)
Background: Mortality from suicide and other causes is significantly increased in patients who engage in self-harm, but their long-term morbidity and quality of life are poorly defined. As the majority of self-harm patients are under the age of 35 years, understanding their longer term health outcomes is important if we are to adequately manage their care. The aim of this study was to investigate the long-term mortality, morbidity and quality of life of such patients. Method: A representative cohort of patients who had presented to hospital following an episode of self-harm was traced after 6 years. Mortality and repetition of self-harm were primary outcome measures. Psychiatric morbidity and indices of quality of life, and social functioning were also obtained. Results: 143/150 (95.3%) patients were traced after a mean of 6.2 years. Eight (5.6%) had died during follow-up, significantly more than general population estimates (p≤0.001), four of these (2.8%) by probable suicide. Further self-harm occurred in 58/101 (57.4%) participants; 70/97 (72.2%) fulfilled criteria for at least one psychiatric disorder, and 51.3% screened positive for harmful use of alcohol. Measures of health status (EQ-5D and SF36-11) were significantly lower (p<0.001) than in the general population. Limitations: Due to the nature of this population group the attrition rate at 6 years is high; although this is the most complete such study to date. Conclusion: Despite positive outcomes in some patients, overall levels of mortality, morbidity, and harmful use of alcohol are high, whilst quality of life is reported as low. This has significant implications for the long-term management of this group.